0=(11x-72)(-8x+44)

Simple and best practice solution for 0=(11x-72)(-8x+44) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0=(11x-72)(-8x+44) equation:


Simplifying
0 = (11x + -72)(-8x + 44)

Reorder the terms:
0 = (-72 + 11x)(-8x + 44)

Reorder the terms:
0 = (-72 + 11x)(44 + -8x)

Multiply (-72 + 11x) * (44 + -8x)
0 = (-72(44 + -8x) + 11x * (44 + -8x))
0 = ((44 * -72 + -8x * -72) + 11x * (44 + -8x))
0 = ((-3168 + 576x) + 11x * (44 + -8x))
0 = (-3168 + 576x + (44 * 11x + -8x * 11x))
0 = (-3168 + 576x + (484x + -88x2))

Combine like terms: 576x + 484x = 1060x
0 = (-3168 + 1060x + -88x2)

Solving
0 = -3168 + 1060x + -88x2

Solving for variable 'x'.

Combine like terms: 0 + 3168 = 3168
3168 + -1060x + 88x2 = -3168 + 1060x + -88x2 + 3168 + -1060x + 88x2

Reorder the terms:
3168 + -1060x + 88x2 = -3168 + 3168 + 1060x + -1060x + -88x2 + 88x2

Combine like terms: -3168 + 3168 = 0
3168 + -1060x + 88x2 = 0 + 1060x + -1060x + -88x2 + 88x2
3168 + -1060x + 88x2 = 1060x + -1060x + -88x2 + 88x2

Combine like terms: 1060x + -1060x = 0
3168 + -1060x + 88x2 = 0 + -88x2 + 88x2
3168 + -1060x + 88x2 = -88x2 + 88x2

Combine like terms: -88x2 + 88x2 = 0
3168 + -1060x + 88x2 = 0

Factor out the Greatest Common Factor (GCF), '4'.
4(792 + -265x + 22x2) = 0

Factor a trinomial.
4((11 + -2x)(72 + -11x)) = 0

Ignore the factor 4.

Subproblem 1

Set the factor '(11 + -2x)' equal to zero and attempt to solve: Simplifying 11 + -2x = 0 Solving 11 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -2x = 0 + -11 Combine like terms: 11 + -11 = 0 0 + -2x = 0 + -11 -2x = 0 + -11 Combine like terms: 0 + -11 = -11 -2x = -11 Divide each side by '-2'. x = 5.5 Simplifying x = 5.5

Subproblem 2

Set the factor '(72 + -11x)' equal to zero and attempt to solve: Simplifying 72 + -11x = 0 Solving 72 + -11x = 0 Move all terms containing x to the left, all other terms to the right. Add '-72' to each side of the equation. 72 + -72 + -11x = 0 + -72 Combine like terms: 72 + -72 = 0 0 + -11x = 0 + -72 -11x = 0 + -72 Combine like terms: 0 + -72 = -72 -11x = -72 Divide each side by '-11'. x = 6.545454545 Simplifying x = 6.545454545

Solution

x = {5.5, 6.545454545}

See similar equations:

| 20+19=19+20 | | 6x^2+11x-16=x+8 | | 9-2n=7+5n-12 | | 52+52+25-102= | | (x/y)-(x/z) | | y=Ix-3I-1 | | -4c+3-4c=-2+2c | | cos(2x-pi/4)=sqrt2/2 | | S(s-3)(s+8)=0 | | 0=3x^2-18x+6 | | 7x-X-X=-8-3x | | 4x^2-4x-7+5x^2-8x-2= | | h=5t^2-10t | | H=5t^2-10 | | 120=1/2[360-x)-x] | | -3(x+2)=2(x+5) | | (x^2-25)(2x+3)=0 | | 2x+3x-41=0 | | 115=x*9.8 | | 8-(2x+5)= | | N/2-6=-3 | | 1300x+500y=234500 | | 5x-2x=49 | | a+(7+6)=(a+7)+6 | | 33-5x=3x+1 | | 13x+5y=2345 | | -5x-9=6x-97 | | v=4/3*3.14*(9)3 | | v=4/3*3.14*(6)3 | | 0=4(15t-4t^2) | | 4b-7-3b=9 | | 0=4(15t-47) |

Equations solver categories